2012
DOI: 10.1007/s00259-011-2021-8
|View full text |Cite
|
Sign up to set email alerts
|

Using PET with 18F-AV-45 (florbetapir) to quantify brain amyloid load in a clinical environment

Abstract: PurposePositron emission tomography (PET) imaging of brain amyloid load has been suggested as a core biomarker for Alzheimer’s disease (AD). The aim of this study was to test the feasibility of using PET imaging with 18F-AV-45 (florbetapir) in a routine clinical environment to differentiate between patients with mild to moderate AD and mild cognitive impairment (MCI) from normal healthy controls (HC).MethodsIn this study, 46 subjects (20 men and 26 women, mean age of 69.0 ± 7.6 years), including 13 with AD, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(182 citation statements)
references
References 42 publications
7
170
0
2
Order By: Relevance
“…This value of 0.69 is similar to the value in another study with 5 readers visually assessing 59 cases ( ϭ 0.76) and in a study with 2 readers visually assessing 46 cases ( ϭ 0.71). 17 The values of our study are also similar to those seen with other ␤-amyloid imaging agents such as 11 C Pittsburgh compound-B. 26 The impact of the data of SUVr on values reported here is also higher than those seen in interobserver variability studies in lesion detection in other organ systems, for example, in the detection of pulmonary nodules with ( ϭ 0.67) 27 and without the use of computer-assisted detection software ( ϭ 0.64) 28 and the detection of breast lesions by using automatic breast scanners ( ϭ 0.8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This value of 0.69 is similar to the value in another study with 5 readers visually assessing 59 cases ( ϭ 0.76) and in a study with 2 readers visually assessing 46 cases ( ϭ 0.71). 17 The values of our study are also similar to those seen with other ␤-amyloid imaging agents such as 11 C Pittsburgh compound-B. 26 The impact of the data of SUVr on values reported here is also higher than those seen in interobserver variability studies in lesion detection in other organ systems, for example, in the detection of pulmonary nodules with ( ϭ 0.67) 27 and without the use of computer-assisted detection software ( ϭ 0.64) 28 and the detection of breast lesions by using automatic breast scanners ( ϭ 0.8).…”
Section: Discussionmentioning
confidence: 99%
“…Cortex-to-wholecerebellum SUVr values were automatically calculated and presented by the software for 6 anatomically relevant cortical ROIs: frontal lobe, lateral parietal lobe, lateral temporal lobe, precuneus, and anterior and posterior cingulate gyrus, as well as the mean SUVr of these regions. 12 Prior studies demonstrated that with the aid of the average SUVr from these anatomic regions, sensitivity and specificity of reads increased by using both clinical diagnosis 17 and pathology 7 as comparisons. Although we chose to use the Scenium software to calculate SUVr, commercial programs from other vendors are available for calculating SUVr.…”
Section: Image Analysis and Reader Studymentioning
confidence: 99%
“…18,19 This approach provides data for calculation of the SUVR between amyloid-rich target regions and an amyloid-free reference region. In the standard quantification procedure, the regional radioactivity concentration is first converted to standardized uptake values (SUVs) typically by a global normalization involving a division with total injected radioactivity and multiplication with body weight.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that image quantitation could be helpful in assisting visual interpretation of PET amyloid images [10][11][12][13]. Quantitation has been applied extensively in other realms of nuclear medicine imaging including PET [14][15][16][17], and quantitative analyses have proven useful for characterizing amyloid tracer binding and relationships to other biomarkers [18][19][20].…”
Section: Introductionmentioning
confidence: 99%